A study on factors that influence social problems among higher learning institutions students in Malacca Tengah - Ismail, Ainor Ashikin; Zainal, Durrani Hakimah (2008)
A social problem is a condition that at least some people in a community view as being undesirable. Every newspaper filled with stories about undesirable social conditions. Examples include crime, violence, drug abuse, and environmental problems. Such social problems happened at the local, state, national and international levels. The increase in the crime rate is not good for the country, the economy will be affected and foreign tourists, and investors will be discouraged from coming. Police need to use new methods and approaches in solving criminal cases. The public must not assume that it is the sole responsibility of the police to protect the community from criminal activities. The public must cooperate with the police by giving information on illegal activities. The recommendation by Higher Education Minister Datuk Seri Mustapa Mohamed for universities to have cultural societies based on races should be welcomed. The formation of cultural societies will help the university students to fully understand and respect their own cultures and beliefs, Tamil Nesan reported (www.thestarsonline.com).